Bicalutamide 50 mg monotherapy in patients with isolated high-grade PIN: findings in repeat biopsies at 6 months. Issue 4 (5th July 2006) - Bono, Aldo V; Mazzucchelli, Roberta; Ferrari, Ilaria; Lopez-Beltran, Antonio; Galosi, Andrea B; Cheng, Liang; Montironi, Rodolfo
Abstract : Objectives: To evaluate morphological findings in repeat biopsies in patients with isolated high-grade prostatic intraepithelial neoplasia (HGPIN) after a 6-month course of bicalutamide (Casodex) 50 mg/day. Methods: 20 consecutive patients with isolated HGPIN in prostate biopsies were treated for 6 months with bicalutamide 50 mg/day. After treatment, the patients were resubmitted to prostate biopsy mapping. The control group included 22 untreated consecutive patients with isolated high-grade PIN with repeat biopsies taken 6 months after the initial biopsies. Results: In the initial biopsies of the treated group, HGPIN was monofocal in 12 patients and plurifocal in 8. In the repeat biopsies HGPIN was present in 2 patients, monofocal in both, whereas prostate adenocarcinoma (PCa) was discovered in one. In the control group, HGPIN was monofocal in 15 and plurifocal in 7. In the repeat biopsies HGPIN was present in six patients, being monofocal in three and plurifocal in the other three. PCa was present in one. Conclusions: There was a lower incidence of HGPIN (treated group vs control: 10% vs 27.2%) after 6 months of bicalutamide. Reduction in its extent was also observed (treated group vs control: monofocal 100% vs 50%). Treatment did not affect the incidence of cancer (treated vs control: 5% vs 4.5%).